Typisierung von Bezirken der Agenturen für Arbeit - Uwe Blien; Franziska Hirschenauer; Manfred Arendt; Hans Jürgen Braun; Dieter-Michael Gunst; Sibel Kilcioglu; Helmut Kleinschmidt; Martina Musati; Hermann Roß; Dieter Vollkommer; Jochen Wein (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2004)
– In a project group of the Federal Employment Service, two classification systems were developed for categorizing employment office areas, one with five and the other with twelve types. The former is intended for the development of strategies of labour market policy; the latter serves to facilitate comparison of the areas themselves. Both are consistent, as the more precise division can be converted into the more approximate one by means of combination. Causal analyses of the exogenous determinants of the success of labour market policy form the basis of the classification. An innovative methodical approach is based on the linking of regression and cluster analyses. The types are now used in the Federal Employment Service for practical tasks of labour market policy, decentralised management and controlling purposes. The classification is also of scientific interest. The empirical diversity of regional disparities is reduced to just a few types which are, however, meaningful.
Keywords: 330; Arbeitsagenturbezirke - Typologie; Benchmarking - Indikatoren; regionaler Vergleich; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland